Impact of Intrapartum Antibiotic Prophylaxis on Offspring Microbiota - Prescott, S.; Dreisbach, C.; Baumgartel, K.; Koerner, R.; Gyamfi, A.; Canellas, M.; St. Fleur, A.; Henderson, W. A.; Trinchieri, G. (Frontiers in Pediatrics, 2021)
Infants are born into a world filled with microbes and must adapt without undue immune response while exploiting the microbiota’s ability to produce otherwise unavailable nutrients. The process by which humans and microbes establish this relationship has only recently begun to be studied with the aid of genomic methods. Nearly half of all pregnant women receive antibiotics during gestation to prevent maternal and neonatal infection. Though this has been largely successful in reducing early-onset sepsis, we have yet to understand the long-term consequences of antibiotic administration during gestation to developing infants. Studies involving antibiotic use in infants suggest that dysbiosis during this period is associated with increased obesity, allergy, and chronic diseases in adulthood, however, research around the limited doses of intravenous antibiotics used for intrapartum prophylaxis is limited. In this review, we focused on the state of the science regarding the effects of antibiotic prophylaxis on the newborn microbial colonization process. Although, the literature indicates that there is wide variety in the specific bacteria that colonize infants from birth, antibiotic administration prior to delivery consistently affects the microbiota of infants by decreasing bacteria in the phylum Bacteroidetes and increasing bacteria in the phylum Proteobacteria, thus altering the normal pattern of colonization that infants experience. Delivery by cesarean section and formula feeding enhance and prolong this effect. Our review shows that the impact of antibiotic administration during gestation has on early colonization, growth, or immune programming in the developing offspring has not been well studied in human or animal models.